Deviants or “Normal” Citizens? : Framing of LGBTQ in Malaysian Newspapers - Ting, Su Hie; Collin, Jerome; Yeo, Jiin Yih (De La Salle University, 2023)
The study examined the framing of LGBTQ in four newspapers in Malaysia. The search uncovered 60 articles on LGBTQ published from January 1 to December 31, 2019 in four online newspapers, namely, MalaysiaKini, The Star Online, Free Malaysia Today, and Astro Awani Online. MalaysiaKini attributed the greatest salience to LGBTQ both in article number and length. LGBTQ was mostly covered using episodic framing (72.73%–91.67%). There were significant differences among the four newspapers on the dominant frames used for representing LGBTQ. The most-used frame was morality in the articles published by the alternative newspapers, but the constitution and jurisprudence frame dominated in the mainstream newspaper, The Star. The four newspapers were similar in their reliance on human rights groups and politicians as information sources. The voices of LGBTQ are muted, implying that they have been sidelined as members of society who cannot assert their rights to speak. Some articles were written in a positive tone in The Star, Free Malaysia Today, and MalaysiaKini, but there were no articles with positive valence in Astro Awani. Negative valence dominated in LGBTQ coverage, reflecting the disapproval of LGBTQ in Malaysia where Islam is the official religion and homosexuality is banned. The findings suggest that dominant frames and valence are constructed through a selective choice of information sources in the context of cultural factors that are at play.